Utilization of Mycophenolic Acid, Azathioprine, Tacrolimus, Cyclosporin, Sirolimus, and Everolimus: Multinational Study - Majda Sahman; Majda Sahman; Snezana Mugosa; Snezana Mugosa; Nemanja Rancic; Nemanja Rancic (Frontiers Media S.A., 2021)
Background: Organ transplantations are difficult, complicated and very expensive interventions. In order to preserve the transplanted organs, it is necessary to provide medical care to the patients in terms of immunosuppression. According to the guidelines, the first-line therapy choices for achieving immunosuppression after transplantation are tacrolimus, cyclosporine, mycophenolic acid, azathioprine, sirolimus, everolimus" and corticosteroids. The aim of our study was to examine the utilization of this drugs in Montenegro and to compare the results with the ones from Finland, Croatia, and Serbia.Methods: In our investigation we used Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) methodology. Prices per DDD of drugs are presented in euros (€).Results: In all observed countries, there is a positive trend in the consumption of all 6 drugs during the analyzed period. The prices per DDD of these drugs generally show a negative trend. Tacrolimus and mycophenolic acid in Montenegro recorded the largest reduction in the price per DDD. Price per one DDD of tacrolimus decreased from €13.28 in 2009 to €5.11 in 2019, thus by about 260%, and as regards mycophenolic acid, the price per one DDD decreased from €9.59 in 2009 to € 3.36 in 2019, thus by almost 300%.Conclusion: Despite the reduction in the price per DDD, drugs that are used as immunosuppressants are showing increasing costs from year to year. Since these drugs are expensive, they participate in a significant percentage in the budget for medicines in each country.